Computational genome-wide identification of heat shock protein genes in the bovine genome [version 1; referees: 2 approved, 1 approved with reservations] - Oyeyemi O. Ajayi; Sunday O. Peters; Marcos De Donato; Sunday O. Sowande; Fidalis D.N. Mujibi; Olanrewaju B. Morenikeji; Bolaji N. Thomas; Matthew A. Adeleke; Ikhide G. Imumorin (F1000Research, 2018)
Background: Heat shock proteins (HSPs) are molecular chaperones known to bind and sequester client proteins under stress. Methods: To identify and better understand some of these proteins, we carried out a computational genome-wide survey of the bovine genome. For this, HSP sequences from each subfamily (sHSP, HSP40, HSP70 and HSP90) were used to search the Pfam (Protein family) database, for identifying exact HSP domain sequences based on the hidden Markov model. ProtParam tool was used to compute potential physico-chemical parameters detectable from a protein sequence. Evolutionary trace (ET) method was used to extract evolutionarily functional residues of a homologous protein family. Results: We computationally identified 67 genes made up of 10, 43, 10 and 4 genes belonging to small HSP, HSP40, HSP70 and HSP90 families respectively. These genes were widely dispersed across the bovine genome, except in chromosomes 24, 26 and 27, which lack bovine HSP genes. We found an uncharacterized outer dense fiber (ODF1) gene in cattle with an intact alpha crystallin domain, like other small HSPs. Physico-chemical characteristic of aliphatic index was higher in HSP70 and HSP90 gene families, compared to small HSP and HSP40. Grand average hydropathy showed that small HSP (sHSP), HSP40, HSP70 and HSP90 genes had negative values except for DNAJC22, a member of HSP40 gene family. The uniqueness of DNAJA3 and DNAJB13 among HSP40 members, based on multiple sequence alignment, evolutionary trace analysis and sequence identity dendrograms, suggests evolutionary distinct structural and functional features, with unique roles in substrate recognition and chaperone functions. The monophyletic pattern of the sequence identity dendrograms of cattle, human and mouse HSP sequences suggests functional similarities. Conclusions: Our computational results demonstrate the first-pass in-silico identification of heat shock proteins and calls for further investigation to better understand their functional roles and mechanisms in Bovidae.